Education of Entrepreneurial Innovation Mediation among Marketing Strategies and Business Sustainability in Ethiopia - Gashaw Habtewold; Jarso Nura Dullacha; Shashi Kant (Research Synergy Foundation, 2023)
The purpose of the current study was to examine the impact of marketing strategies on the growth of sustainable businesses in the context of entrepreneurial innovation education during the innovation phase. To achieve this, the researchers employed both descriptive and inferential statistics along with various techniques. They utilized probability and non-probability sampling methods, employing a straightforward random sampling mechanism. Data for the study were collected from the Addis Ababa branch of the Digital Banking Sector's Ethiopian commercial bank branch, which served as the representative organization. A survey was conducted among 425 clients of the Digital Banking Sector, including individuals from various sectors and personnel from contemporary organizations. Theresults of the study revealed that insufficient leadership capabilities, unfavorable work environments, and low employee engagement were the main factors contributing to decreased business sustainability and hindered implementation of marketing strategies. Based on their findings, the researchers recommended that relevant authorities take action to address these issues, including improving the implementation of marketing strategies, addressing the identified predictors, and promoting strong business sustainability.